O elemento vegetal e a ambiência na Avenida Goiás : estudo de caso do trecho histórico original - Silveira, John Mivaldo da (2007)
The present work, developed under the theme - The vegetal element and the ambience of the Goiás Avenue, the analysis of its original historical part - is carried in a first moment with a criticaI analysis and a theoretical review of this subject. In a second moment the present study is carried with the collection and analysis of data about climatic and morphological aspects. pollution, and urban topology. These data were used to refine the performance of the vegetal element and the characteristics of the urban ambience in the original historical part of the Goiás Avenue. which is significant and represents an identity to the population of Goiânia. The choice of the theme is justified by the importance that the vegetation and the environmental matters have assumed in the process of development and administration of the cities. as well as the role which the city of Goiânia has played about this subject since its foundation as a planned city (1933) The theme emphasizes the arboreal questions and its influence in the urban ambience, which are presented as the essence of the research. The objectives of the work required a total understanding of the different historical periods of the city and for that some studies already completed regarding classification were used About the spatial range of the empiric object. (the Goiás Avenue) its original and most significant part was chosen as the object of this research. which is comprehended from the Civic Square until the Paranaíba Avenue. Some hypotheses were primarily raised, one of them is that the Goiás Avenue settles itself as a potential element of synthesis and representation of the collective memory of the city of Goiânia. requiring as that a meaning of identity to its population. Another hypothesis is that the initial reasons that leaded to the conception of the Avenue are being lost along the time with the transformations of the morphological components, generating the 1055 of its characteristics and a considerablelement of composition and of definition of the performance of ambience in the urban environment including the one analyzed by the present work. and therefore. making its perception and appropriation by the population ane 1055of its ambience- Yet it is presented the hypothesis that the vegetation was and it still being an important important aspect in the urban planning of the city. The hypothesis here presented, with a bigger or smaller degree of evidence. were confirmed after the analysis and interpretation of the data collected.